Competition and fatigue at work - Vera Angelova; Thomas Giebe; Radosveta Ivanova-Stenzel (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
We study theoretically and experimentally the role of fatigue and recovery within a competitive work environment. At work, agents usually make their effort choice in response to competition and monetary incentives. At the same time, they have to take into account fatigue, which accumulates over time if there is insufficient recovery. We model a sequence of work periods as tournaments that are linked through fatigue spillovers, inducing a non-time-separable decision problem. We also allow for variations in incentives in one work period, in order to analyze spillover effects to the work periods "before" and "after". Making recovery harder should, generally, reduce effort. This theoretical prediction is supported by the experimental data. A short-term increase in incentives in one period should lead to higher effort in that period, and, due to fatigue, to strategic resting before and after. Our experimental results confirm the former, whereas we do not find sufficient evidence for the latter. Even in the presence of fatigue, total effort should positively respond to higher-powered incentives. This is not supported by our data. Removing fatigue, we find the expected increase in total effort. For work environments, this may imply that the link between monetary incentives and effort provision becomes weaker in the presence of fatigue or insufficient recovery between work periods.
Keywords: C72; C91; D9; J22; J33; M5; M52; 330; fatigue; recovery; incentives; experiment; tournament